Assessing Head Teachers’ Distributed Leadership Practices in Public Secondary Schools of Kathmandu Valley (Pathibhara Journal of Multidisciplinary Research, 2026)
This study examines the distributed leadership practices of head teachers in public secondary schools within the Kathmandu valley. The objective of study was to assess relationship between demographical variables of head teachers and their distributed leadership. In doing so, the study adopted survey research approach within a quantitative research design based on the post-positivism philosophical paradigm. Required data for the study were collected from 165 head teachers; including 97 from Kathmandu, 41 from Lalitpur and 27 from Bhaktapur selected randomly by using self-administered survey questionnaires. The research instrument comprised two sections: a demographic questionnaire and a 43-item five-point Likert scale measuring five distributed leadership attributes— sharing (9 items), collective (9 items), collaborative (8 items), co-leader (7 items), and democratic practices(10 items)—adapted from previous studies. The study foregrounds significant differences between head teachers’ distributed leadership practice and demographic variables in qualification and training status. The training status was found significant difference in collaborative, coleader, collective and distributed leadership where p- value was found < 0.05. The level of HTs’ found moderate in gender, experience in position, districts wise leadership, teaching experience, training days and attributes wise leadership. The Head Teachers’ distributed leadership supports the holistic schools’ productivity and progress in terms of quality education. Head Teachers can no longer do their jobs alone. The Head Teachers’ distributed leadership can enhance the better result of Schools.